Pembajakan Produk: Dilema Budaya antara Barat dan Timur Kajian Literatur pada Sisi Permintaan - Anas Hidayat; Ian Phau (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2003)
Consumers are the actual force behind the counterfeiting trade. The main problem of the demand side is clearly an issue of consumer misbehaviour. Such behaviour is potentially harmful to business, the consumers themselves, and society as a whole. Astonishingly, Asian people who constitute the majority of the world’s population support this activity. Asian people generally have low expectations of branded products, because they tend to blindly believe that foreign brands are best, and they do not distinguish among different brands. It is possible that most of the Intellectual Property Rights (IPR) infringements taking place in Asian countries may stem from cultural differences in morality and perspective between people in the East and the West. Asian cultures have traditionally emphasized that individual developers or creators are obliged to share their developments with society. IPR, on the other hand, reflects a characteristic value of the Western World in general. Indeed, some Asian nations seem to believe that IPR is a Western concept created to maintain a monopoly over the distribution and production of knowledge and knowledge based products. As a result, when foreign countries on Asian countries to develop laws to counter trademark infringements place pressure, counterfeit products have not diminished.In relation to the demand for acknowledgment of original works of human intellect and the magnitude of the protection of intellectual property rights, the Indonesian Government has taken a number of considerable measures in establishing and improving the intellectual property rights system, with regards to its worldwide obligations as approved in the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement, as one of the agreements of the World Trade Organisation (WTO). In fact, Intellectual Property Rights (IPR) has become one of the essential means of the global trade.